Radiation model for predicting temperature evolution in solar cooker (2011)
A mathematical model that describes and simulates the thermal behavior of a solar stove was developed based on an electric resistances analogy. The mathematical model includes the three different heat transfer mechanisms between different surfaces of the solar stove and its environment. The mathematical model was used to predict the solar stove entropy generation and its efficiency; also, it was used to evaluate the design parameters of a solar box stove. Experimental and theoretical data were compared and found to be satisfactory.